PERAN SELF EFFICACY, GAYA BELAJAR, DAN KESADARAN METAKOGNITIF DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Gea Awaliyah; Yoni Hermawan; Ai Nur Solihat (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of self efficacy, learning style, and metacognitive awareness on critical thinking skills in economic subjects. The research method used is a survey method with an associative research design. The population in this study were grade XI students at SMA Negeri 5 Tasikmalaya City who took economics subjects totaling 116 people. Sampling using saturated samples. The data collection technique used in this study was a questionnaire and the data analysis technique used was multiple linear regression analysis. The results showed that there is a positive and significant influence between self efficacy on critical thinking ability; there is a positive and significant influence between learning styles on critical thinking ability; there is a positive and significant influence between metacognitive awareness on critical thinking ability; and there is a positive and significant influence between self efficacy, learning styles and metacognitive awareness on critical thinking ability.